Effective thermal conductivity of porous materials and composites as a function of fundamental structural parameters - Asakuma, Yusuke; Yamamoto, Tsuyoshi (Computer Assisted Methods in Engineering and Science, 2013)
We conducted thermal conductivity investigations by homogenization. This method can effectively model structural features such as pores within dispersed particle architectures via a finite element mesh. We investigated the factors that determine the effective thermal conductivity of porous structures and composites, such as the volume ratio of the continuous and dispersed phases, conductivity ratio, Biot number and particle packing model.